Analisis Usability Aplikasi Pengolahan Data Berbasis Web Pada Perpustakaan Sekolah Berdasarkan Permodelan Nielsen - Dedy Kurniawan; M. Rudi Sanjaya; Ahmad Rifai; Sutarno Sutarno (Generic, 2021)
Web-based data processing applications have an important role to avoid human error, especially in school libraries. However, in developing a system, consideration of the level of user satisfaction is needed. So the purpose of this study is to analyze the usability of web-based data processing applications in school libraries based on Nielsen's modeling. The method of data collection was performed through filling out questionnaires by 51 students of Public Junior High School 2 Jejawi, OKI Regency. The questionnaire consists of 15 questions using a 4-point Likert scale. The results obtained indicate that the data are valid and reliable. In addition, the web-based data processing application shows that the five usability attributes of Nielsen, namely learning ability, efficiency, memories, few error, and satisfaction have good results, with an average usability score of 80.4. In conclusion, web-based processing applications are acceptable